Pengaruh Model Pembelajaran CORE (Connection, Organizing, Reflecting, Extending) Terhadap Pemahaman Konsep Matematika Siswa - Sheilla Rosalline; Mailizar Mailizar; Lasia Agustina (Universitas Indraprasta PGRI, 2019)
The purpose of this research is to determine the implementation of the CORE type of Cooperative learning model for understanding students ' mathematical concepts. The research method used in this research is the quasi-experimental method. Where experiment classes use the Core Type Cooperative learning model and control class using AIR type Cooperative. Instrument in this research is a question of essay-form. The test instruments used are validity tests and reliability tests. In the hypothesis test using test-T obtained the value of t_hitung > t_ (table) (3,925 > 2,0021), meaning understanding of the mathematical concepts of students taught with a cooperative model of type cooperatives is higher than those taught with models WATER-type cooperative learning to prove that there is an influence on the model of CORE cooperative Learning to understand the mathematical concepts of students.